Judicial Creativity And Preventive Detention In India: An Aspect Of Indian Constitutional And Administrative Law - Jain, M.P. (Journal of Malaysian and Comparative Law, 2018)
Judicial Creativity And Preventive Detention In India: An Aspect Of Indian Constitutional And Administrative Law